2009
DOI: 10.3133/sir20095047
|View full text |Cite
|
Sign up to set email alerts
|

Fish Communities and Habitat of Geomorphically Stable Reference Reaches in Streams of the Catskill Mountain Region, New York

Abstract: Diagram showing mean, median, 95th percentile, 75th percentile, 25th percentile, and 10th percentile for (A) total biomass, (B) brown trout density, (C) rainbow trout density, (D) brown trout biomass, (E) rainbow trout biomass, (F) brook trout density, and (G) brook trout biomass, separated by Rosgen stream type .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Although small headwater streams generally have fewer species and lower diversity and equitability than larger streams (Lyons et al 1996), Daniels et al (2002) found that as many as 13 fish species occur in the headwater streams of the Catskill Mountain region. These findings and the state of fish populations and communities at undisturbed reaches in this region (Baldigo and Lawrence 2001;Mulvihill et al 2009) indicate that NCD restorations would increase community richness, equitability, and biomass and possibly decrease community density, assuming that increased stability improves habitat quality. The effects of NCD restoration on the density and biomass of individual species (especially brown, brook, and rainbow trout [native or introduced]) were important because these species are top predators and important game fish in the region.…”
mentioning
confidence: 79%
“…Although small headwater streams generally have fewer species and lower diversity and equitability than larger streams (Lyons et al 1996), Daniels et al (2002) found that as many as 13 fish species occur in the headwater streams of the Catskill Mountain region. These findings and the state of fish populations and communities at undisturbed reaches in this region (Baldigo and Lawrence 2001;Mulvihill et al 2009) indicate that NCD restorations would increase community richness, equitability, and biomass and possibly decrease community density, assuming that increased stability improves habitat quality. The effects of NCD restoration on the density and biomass of individual species (especially brown, brook, and rainbow trout [native or introduced]) were important because these species are top predators and important game fish in the region.…”
mentioning
confidence: 79%